Effects of Electric Fields on the Switching Properties Improvements of RRAM Device With a Field-Enhanced Elevated-Film-Stack Structure - Kai-Chi Chuang; Kuan-Yu Lin; Jun-Dao Luo; Wei-Shuo Li; Yi-Shao Li; Chi-Yan Chu; Huang-Chung Cheng (IEEE Journal of the Electron Devices Society, 2018)
In this paper, a resistive random access memory (RRAM) device using a field-enhanced elevated-film-stack (EFS) structure with a 15-nm-thick HfOx dielectric layer was fabricated and measured to achieve a forming voltage (VForming) of 2.04 V, set voltage (VSet) of 0.95 V, and reset voltage (VReset) of -1.22 V, compared to the values of 2.73 V, 1.26 V, and -1.54 V for the planar one with 6-nm-thick HfOx, respectively. These resistive switching characteristics were effectively reduced, and the uniformity of these characteristics from device to device were considerably improved. The improvements of such an EFS-structured RRAM device were attributed to the high local electric fields at the two sharp corners of the EFS structure, which facilitated the formation of conductive filaments, and the distribution of the electric field was verified by technology computer-aided design simulations.